Instal·lació o establiment? Encara sobre els objectius de la promoció lingüística - Lamuela, Xavier (Caplletra. Revista Internacional de Filologia, 2004)
This article suggests a criticism on the “language normalization” concept,focusing on the dichotomy establishment (adquisition of a complete referential value) and installation (partial language standardization). The author defends the idea that Catalan can try to strengthen its status as installed language, but it will hardly attain the absolute preeminence of an established language. Its perspective is compatible with notions like “llengua pròpia” (own language) or territorial language and clashes with the neoliberals, who defend utilitarist and pseudonaturalist concepts like maximalist monolinguism.